Analysis of alternative road construction staging approaches to reduce carbon dioxide emissions. (1st February 2017) - Krantz, Jan; Lu, Weizhuo; Johansson, Tim; Olofsson, Thomas
Abstract: Despite many studies focusing on assessing energy use and carbon dioxide emissions in road projects, limited attention has been given to practical methods for mitigating environmental impacts at the project planning stage. Our study addresses this issue by proposing a model incorporating a step-by-step guide for calculating carbon dioxide emissions in the project. This model is practically applied to a road construction project where two major supply chain alternatives are evaluated and compared. The findings suggest that major reductions of carbon dioxide emissions can be achieved by (1) identifying and comparing a set of realistic project alternatives, and (2) conducting this at an early stage of the project planning process so that favorable alternatives can be implemented during construction. Highlights: A model for evaluating and reducing CO2 emissions in road construction is proposed. A set of project alternatives to reduce CO2 emissions are evaluated. Alternatives to reduce CO2 emissions should be evaluated at early project stages.